URBAN ECOTOURISM: TANTANGAN DALAM MENINGKATKAN PARTISIPASI MASYARAKAT KAMPUNG WISATA KOTA BOGOR - Helianthi Dewi; Occy Bonanza; Bedi Mulyana; Insan Kurnia; Dyah Prabandari (Bogor Hospitality Journal, 2023)
The success of urban ecotourism in tourism villages requires community participation, both in developing tourism activities and businesses and in tourism management. The research aims to analyze three aspects, namely natural and cultural potential, the obstacles faced by the community in managing tourism villages, and the potential for community participation in managing tourism villages. The research was conducted in two tourism villages located in the center of Bogor City, namely Pulo Geulis Village and Labirin Village. Primary data was collected by distributing questionnaires to community respondents and analyzed descriptively using the Kruskal Wallis test. The study shows that cultural potential is more likely to be utilized in an effort to improve the community's economy and attract tourist visits. Community participation is still limited to Kompepar membership and food and beverages providers. The low participation is strongly suspected because the income derived from the tourism business is still unable to meet daily needs. Continuous coaching and increasing synergy between communities in tourism villages is an important thing to do to increase community participation in tourism development.